Análisis geoestadístico de la Aleurocanthus woglumi (Hemiptera: Aleyrodidae) en la agrosilvicultura y el monocultivo en la Amazonía Oriental - Gonçalves da Silva, Anderson; S. Farias, Paulo Roberto; Silva Siqueira, Diego [UNESP]; Boiça Junior, Arlindo L. [UNESP] (My University, 2014)
This work aimed to analyze the spatial and temporal distribution of citrus blackfly (Aleurocanthus woglumi) infestation in citrus farms in agroforestry and monoculture systems using geostatistics methodology to help the sampling optimization. The experimental area is located in Capitão Poço, Pará State, Brazil, where twelve samplings were taken from September 2008 to October 2009, evaluating the presence or absence of the pest in orange trees in both production systems. The citrus blackfly spatial distribution showed a grouping pattern, clustered in a spatial dependence described as spherical model, forming spots from 8.5 to 34 meters (model’s reach) to both planting systems adopted. The citrus blackfly showed a strong tendency to infest the neighbor plant, forming spots that grow through the planting line. Based on the semivariogram reach parameter, the average number of suggested evaluations along the year for the agroforestry system would be 17 evaluations ha-1 and for the monoculture system seven evaluations ha-1. In the monoculture system, during the dry (from August to November) and the wet (from January to May) seasons the number of evaluations should not vary and seven evaluations ha-1 are recommend. However, in the agroforestry system it is suggested 12 evaluations ha-1 during the wet season and 23 evaluations ha-1 during the dry season.
Aleurocanthus woglumi (Hemiptera: Aleyrodidae) geostatistics analysis in agroforestry and monoculture systems in Oriental Amazon
Keywords: Aleyrodidae; Citrus blackfly; Citrus sinensis; Sampling optimization; Tectona grandis; Variability